Evaluating If Children Can Use Simple Brain Computer Interfaces - Zhang, Jack; Jadavji, Zeanna; Zewdie, Ephrem; Kirton, Adam (Frontiers in Human Neuroscience, 2019)
Background: The ability of severely disabled children with intact cognition to interact with their environment are extremely limited. A brain computer interface (BCI) has the potential to allow such persons to gain meaningful function, communication, and independence. While the pediatric population might benefit most from BCI technology, research to date has been predominantly in adults. Methods: In this prospective, cross-over study, we quantified the ability of healthy school-aged children to perform simple tasks using a basic, commercially available, EEG-based BCI. Typically developing children aged 6-18 years were recruited from the community. BCI training consisted of a brief set-up and EEG recording while performing specific tasks totalling <1 hour. BCI training consisted of a brief set-up and EEG recording using an inexpensive, commercially available BCI system (Emotiv EPOC). Two tasks were trained (driving a remote-control car and moving a computer cursor) each using two strategies (sensorimotor and visual imagery). Primary outcome was the kappa coefficient between requested and achieved performance. Effects of task, strategy, age, and learning were also explored. Results: Twenty-six of out thirty children completed the study (mean age 13.2±3.6 years, 27% female). Tolerability was excellent with >90% reporting the experience as neutral or pleasant. Older children achieved performance comparable to adult studies, but younger age was associated with lesser though still good performance. The car task demonstrated higher performance compared to the cursor task (p = 0.027). Thought strategy was also associated with performance with visual imagery strategies outperforming sensorimotor approaches (p = 0.031). Conclusions: Children can quickly achieve control and execute multiple tasks using simple EEG-based BCI systems. Performance depends on strategy, task and age. Such success in the developing brain mandates exploration of such practical systems in severely disabled children.